An objective assessment of vision performance at different reading distances after smooth incision lenticular keratomileusis (SILK) for myopia - Rohit Shetty; Pooja Khamar; Raghav Narasimhan; Ritika Mullick; Anushree Bhatkal; Anisha Ramesh; Abhijit Sinha Roy (Scientific Reports)
Abstract Differences in lenticule shapes may impact on the design of future presbyopic treatments with lenticule surgery. Hence, the objective of this study was to assess the depth of field of eyes after smooth Incision Lenticular Keratomileusis (SILK) surgery for refractive correction of myopia. In this study, patients who underwent SILK surgery were included. At 6 months, all eyes underwent ocular aberrometry with iTrace aberrometer (Tracey Technologies, USA) while fixating at reading targets [distance, intermediate (60 cm), near (40 cm)]. Data from SILK eyes were compared with emmetropic and laser assisted in-situ keratomileusis eyes from an earlier study. A total of 69 eyes were included. At distance and near, eyes from all groups had similar VA clinically. However, emmetropic and SILK eyes had better VA than LASIK eyes at intermediate distance (P < 0.05). Postoperatively, SILK eyes had a greater cylinder at all distances and had greater proportion of eyes with sphere less than − 0.5D at distance than LASIK eyes (P < 0.05). Similarly, SILK eyes had a greater number of eyes with cylinder between − 0.5 to − 1D than LASIK eyes (P < 0.05). Ocular defocus at intermediate and near distance of the SILK eyes were similar to emmetropic eyes but distinct from LASIK eyes (p < 0.05). Overall, induction of higher order aberrations was minimal after SILK. SILK eyes had better VA at intermediate distance compared to LASIK eyes. Nomogram sphere adjustment was adequate for refractive accuracy of SILK surgery and zero-cylinder adjustment provided better intermediate distance vision than the LASIK eyes.